Land Use-Driven Variation in Soil Physical Properties: A Case Study from Wotan Village, Panceng Subdistrict, East Java - Abid, Moh Mislahul; Maroeto, Maroeto; Arifin, Moch. (Universitas Labuhanbatu, 2025)
Background: The physical characteristics of soil under different land uses influence its potential for optimal productivity. Wotan Village, located in Panceng District, Gresik Regency (part of the northern limestone mountains), can maximize land use by considering the type of crops and land suitability based on soil physical properties. The mismatch in land use in Wotan Village is likely due to poor soil physical properties, as the soil is formed from weathered limestone. Limestone soils are dominated by fine fractions in their texture, and their texture and structure are generally unsuitable for use as planting media. This study aims to analyze the physical characteristics of soils under various land-use types and to determine the effect of different land uses on soil physical properties. Methodology: The research employed a purposive sampling method. Soil samples were collected from three types of land use: plantation, dryland farming, and rainfed rice fields, at two depths (0-20 cm and 20-40 cm) with five replications. Laboratory analyses were conducted on soil physical parameters, including texture, bulk density, particle density, total pore space, and permeability. Findings: The results showed that the soils in the three land-use types had clay loam, silty clay, and clay textures. Bulk density ranged from 1.10 to 1.24 g/cm³ for rainfed rice fields at a depth of 20 cm. Particle density ranged from 2.46 to 2.603 g/cm³. Total pore space ranged from 52.46% to 56.31%. Permeability ranged between 0.80 and 1.21 cm/hour, classified as moderately slow. Differences in land use had no significant effect on soil physical properties. Contribution: The findings provide a reference for farmers regarding the physical properties of soils in limestone areas